Quality scores of outpatient ENT surgery in Centro Hospitalar V. N. Gaia / Espinho - Correia, Valter Melo (2013)
Objectives: To present results of surgery performed at the ENT clinic in C.H. V.N. Gaia/Espinho and their quality scores.Methods: Pediatric Population underwent surgery in ENT clinic in CHVN G / E. between May 2009 and December 2010. We performed a retrospective analysis of data from medical records and telephone survey.Results: We analyzed a population of 121 patients, 40.5% of whom underwent adenotonsillectomy, 21.5% with TTT’s adenoidectomy, adenoidectomy alone 12.4% and 25.6% other. There were no immediate or late complications in 57% and 80.2% of cases. Pain was the most frequent complaint in both periods (32,2%). The overall level of satisfaction was very satisfied in 89.3% of cases.Conclusions: The low complication rate and high level of satisfaction demonstrates the advantages of outpatient surgery in management of resources, quality and safety of services provided.